Religion and hospitality in the television series Homeland - Mike, Laura (AMERICANA E-journal of American Studies in Hungary, 2018)
The purpose of this essay is to show how the trauma of 9/11 and the “war on terror” launched in its wake registers itself in popular culture, through the award-winning Showtime series, Homeland. The two most important aspects I am going to investigate are: 1. the character of the bipolar female protagonist and 2. the debunking of the Islam equals to terrorism myth. In the character of Carrie Matthison the show subverts the stereotypical figure of the invincible white male CIA agent. Additionally, her bipolar disorders render her vulnerable in the most acute situations, thus creating extra suspense in the film. Carrie’s person is the perfect metaphor for after 9/11 US society; the other controversial issue is the alleged Islamophobia of the show. The analysis shows how Homeland represents Muslim religion in a sensitive way, not lending itself to easy stereotyping but allowing for a diversity of representation, thus challenging prejudiced thinking. All these insights are received by understanding the workings of the National Security State within the theoretical frameworks of Jacques Derrida’s hospitality and Slavoj Žižek’s different modes of violence.